Hydrocele of the canal of Nuck - Nourah ALSaleh; Abdulrahman ALMaghrabi; Abdulaziz Banaja (Elsevier, 2018)
Hydrocele of the canal of Nuck is a rare condition in female children caused by a failure of complete obliteration of the canal of Nuck. The canal of Nuck is an abnormal patent pouch of the peritoneum extending anterior to the round ligament of the uterus into the labia majora. Incomplete obliteration of this canal (patent processus vaginalis) can result in either an inguinal hernia or a hydrocele. Here, we report two cases of hydrocele of the canal of Nuck presented within a two-month period. In the first case, incarcerated right-sided inguinal hernia was suspected while the second case was clinically diagnosed as encysted hydrocele of canal of Nuck. Both patients underwent surgical exploration. Hydrocelectomy with high ligation was also performed. One month after the surgery, the first patient showed signs of hydrocele on contralateral side, while the other patient showed no sign of contralateral hydrocele or hernia.